Governing early learning among the American states. (December 2022) - Rauch Griffard, Megan; Sadler, James; Little, Michael; Cohen-Vogel, Lora
Graphical abstract: Abstract: Researchers have posited that possible explanations that contribute to the variability in Pre-K program quality and subsequent mixed results in terms of student outcomes include, among others, an uncoordinated Pre-K delivery system and misalignment between the Pre-K and K-12 sectors. This study investigates one mechanism by which states attempt to resolve challenges resulting from mixed delivery and vertical misalignment: their governance structures, as identified by Kagan's (2015) as one mechanism in the systems-focused model for the provision of high-quality early education. By collecting and analyzing documents from all 50 states, we describe how early learning is governed across the U.S. Finding variability, we organize state governance structures into a five-category taxonomy. We then analyze the mission statement, scope, and goals of each state's early childhood council and find only a small subset address issues related to vertical alignment. The findings take on added significance as Congress debates the American Families Plan, the Biden Administration's initiative that would partner with states to offer free, high-quality preschool to all of the nation's three- and four-year-olds.